ANALISIS PENGARUH CUSTOMER EXPERIENCE TERHADAP PEMBELIAN ULANG (Studi Kasus pada Konsumen Restoran Gudeg Yu Djum Jln. Kaliurang Km. 5 Koncoran Gg. Sri Katon 2 Yogyakarta) - Muhamad Zaenuri; Aftoni Sutanto (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine the effect of the repurchase of Gudeg Yu Djum restaurant. The sample used in this study amounted to 100 respondents, while the sampling method used was purposive sampling method. Data analysis method used is quantitative analysis using validity and reliability tests, F tests, coefficient of determination, t tests and multiple linear regression analysis. Analysis tools using multiple linear regression methods can be concluded that the sense variable has no significant effect on repurchases with a significance value (P value) of 0.840> 0.05, the feel variable has a significant effect on repeat purchases with a significance value (P value) of 0.007 <0 , 05, think variable has a significant effect on repurchase with a significance value (P value) of 0.005 <0.05, Act variable has no significant effect on repurchase with a significance value (P value) 0.945> 0.05, the relate variable has a significant effect on repurchase with a significance value (P value) 0.042 <0.05. Simultaneously sense, feel, think, act, and relate, significantly influence the repurchase with an F count of 22,010 with a significant number (P value) 0,000 <0.005. The coefficient of determination generated is 0.515, which means 51.5% change in the repurchase variable is explained by the variables sense, feel, think, act, and relate together, while the remaining 48.5% is explained by other variables not included in this research.